Datenbewusstsein im Kontext digitaler Kompetenzen für einen selbstbestimmten Umgang mit datengetriebenen digitalen Artefakten - Höper, Lukas; Schulte, Carsten (51. Jahrestagung der Gesellschaft für Informatik, INFORMATIK 2021 - Computer Science & Sustainability, Berlin, Germany, 27. September - 1. Oktober, 2021)

Methodik für Datenprojekte im Informatikunterricht - Höper, Lukas; Hüsing, Sven; Malatyali, Hülya; Schulte, Carsten; Budde, Lea (LOG IN)

Entwicklung eines neuartigen Reinigungsverfahrens für recycelte Kohlenstofffasern - Linnig, Caterina; Tröster, Thomas

In-situ TEM observation of intermetallic phase growth in Al-steel clad sheet - Křivská, Barbora; Šlapáková, Michaela; Minárik, Peter; Fekete, Klaudia; Králík, Rostislav; Stolbchenko, Mykhailo; Schaper, Mirko; Grydin, Olexandr (APPLIED PHYSICS OF CONDENSED MATTER (APCOM 2021))
Aluminum-steel clad composites are used as structural elements in car bodies and chases as well as in the chemical industry due to a combination of high strength of steel, low density of Al and high corrosion resistance of both materials. An important parameter influencing mechanical properties of the composite is the microstructure of the bonding region between Al and steel layer. During manufacturing of the final product, clad sheets can be subjected to elevated temperatures which enhance diffusion between the metals. As a result, a brittle intermetallic phase, deteriorating the bond strength between steel and aluminum, forms at the interface. This paper focuses on study of the interfacial microstructure in a twin-roll cast Al-steel clad strip and its evolution during in-situ annealing in transmission electron microscope. Due to isochronal annealing above 500 °C, Al5Fe2 phase forms at the interface. Nucleation centers formed at the beginning of heating experiment expand and form continuous layer. The kinetics of the growth follows the parabolic law typical for diffusion-controlled phase transformations.

Kovač, Srećko, “Logical Foundations and Kant’s Principles of Formal Logic”, History and Philosophy of Logic 40 (2020) - Peckhaus, Volker (Mathematical Reviews [4053233])

Timing Optimization for Virtual FPGA Configurations - Witschen, Linus Matthias; Wiersema, Tobias; Raeisi Nafchi, Masood; Bockhorn, Arne; Platzner, Marco (Proceedings of International Symposium on Applied Reconfigurable Computing (ARC'21))

Design Principles for a Crowd-Based Prototype Validation Platform - Gottschalk, Sebastian; Aziz, Muhammad Suffyan; Yigitbas, Enes; Engels, Gregor (Software Business - 12th International Conference, ICSOB 2021, Drammen, Norway, December 2-3, 2021, Proceedings)

Situation- and Domain-specific Composition and Enactment of Business Model Development Methods - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Product-focused Software Process Improvement)
Developing effective business models is a complex process for a company where several tasks (e.g., conduct customer interviews) need to be accomplished, and decisions (e.g., advertisement as a revenue stream) must be made. Here, domain experts can guide the choices of tasks and decisions with their knowledge. Nevertheless, this knowledge needs to match the situation of the company (e.g., financial resources) and the application domain of the product/service (e.g., mobile app) to reduce the risk of developing ineffective business models with low market penetration. This is not covered by one-size-fits-all development methods without tailoring before the enaction. Therefore, we conduct a design science study to create a situation-specific development approach for business models. Based on situational method engineering and our previous work in storing knowledge of methods and models in distinct repositories, this paper shows the situation-specific composition and enaction of business model development methods. First, the method engineer composes the development method out of both repositories based on the situational context. Second, the business developer enacts the method and develops the business model. We implement the approach in a tool and evaluate it with a industrial case study on mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Lean Development; Kanban Boards; Canvas Models

Methodenentwicklung zur Versagensanalyse aufgrund der Aushärtung vorgeschädigter Klebverbindungen in stahlintensiven Mischbaustrukturen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Aubel, Tobias; Matzenmiller, Anton (21. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Elektrische Antriebe – Regelung von Antriebssystemen - Schröder, Dierk; Böcker, Joachim

Common-Mode-Free Bidirectional Three-Phase PFC-Rectifier for Non-Isolated EV Charger - Strothmann, Benjamin; Schafmeister, Frank; Böcker, Joachim (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
DC-DC converters for on-board chargers (OBC) of electrical vehicles are usually galvanically isolated allowing modular single-phase PFC front-end solutions, but require transformers which are more bulky, costly and lossy than inductors of non-isolated DC-DCs. Furthermore, for vehicle-to-grid applications, bidirectional converters with transformers are generally more complex and have a higher count on semiconductor switches than transformerless solutions. However, when using non-isolated DC-DC converters within an OBC, the large common-mode (CM) capacitance comprising capacitive parasitics of the traction battery as well as explicit Y-capacitors connecting the high-voltage DC-system (HV-system) within specific HV-loads to ground has to be considered. For the PFC front-end stage, when supplied from the three-phase mains this means that generation of high-frequency and high-amplitude CM voltages, as it is common e.g. with the conventional six-switch full-bridge converter, has to be strictly avoided. For this reason, a modified topology is suggested leading to a different mode of operation and to a very low common-mode noise behaviour: The three-phase four-wire full-bridge PFC with split DC-link, whose midpoint is connected to the mains neutral provides very stable potentials at the DC-link rails and therefore it can be classified as Zero-CM-topology.For dedicated single-phase operation, as required for most OBC, an additional balancing leg may be added to the topology to reduce the required DC-link capacitance and allow non-electrolytic capacitors.The function of the bidirectional Zero-CM three-phase four-wire full-bridge PFC was verified by simulation and on an 11 kW-laboratory sample. The power factor is above 0.999 and an efficiency of 98 % is measured.
Keywords: Three-phase four-wire; OBC; Y2G; PFC; CM; EY charger; balancing circuit

Model Predictive Control of Permanent Magnet Synchronous Motors in the Overmodulation Region Including Six-Step Operation - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Open Journal of Industry Applications)

Temperature estimation of electric machines using a hybrid model of feed-forward neural and low-order lumped-parameter thermal networks - Gedlu, Emebet Gebeyehu; Wallscheid, Oliver; Böcker, Joachim (2021 IEEE International Electric Machines & Drives Conference (IEMDC))

Interleaved Single-Stage LLC Converter Design Utilizing Half- and Full-Bridge Configurations for Wide Voltage Transfer Ratio Applications - Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Design and Analysis of a Regenerative Snubber for a 2.2 kW Active-Clamp Forward Converter with Low-Voltage Output - Korthauer, Bastian; Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))

Transferring Online Reinforcement Learning for Electric Motor Control From Simulation to Real-World Experiments - Book, Gerrit; Traue, Arne; Balakrishna, Praneeth; Brosch, Anian; Schenke, Maximilian; Hanke, Sören; Kirchgässner, Wilhelm; Wallscheid, Oliver (IEEE Open Journal of Power Electronics)

Safe Bayesian Optimization for Data-Driven Power Electronics Control Design in Microgrids: From Simulations to Real-World Experiments - Weber, Daniel; Heid, Stefan; Bode, Henrik; Lange, Jarren; Hüllermeier, Eyke; Wallscheid, Oliver (IEEE Access)

Single-Phase Operation of Common-Mode-Free Bidirectional Three-Phase PFC-Rectifier for Non-Isolated EV Charger with Minimized DC-Link - Strothmann, Benjamin; Book, Gerrit; Schafmeister, Frank; Böcker, Joachim (PCIM Europe digital days 2021; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)
In electric vehicles (EV) the large common-mode (CM) capacitance comprising capacitive parasitics of the traction battery as well as explicit Y-capacitors connecting within specific loads the high-voltage DC-system (HV-system) to ground, can cause issues when using non-isolated EV Chargers. One solution for a power factor correction (PFC) rectifier that is capable to operate with a non-isolated DC-DC converter, is the three-phase four-wire full-bridge PFC, with split DC-link, whose midpoint is connected to the mains neutral. Therefore, it provides very stable potentials at the DC-link rails and accordingly can be classified as Zero-CM topology, which facilitates a common-mode-free operation. When to be operated at a single-phase supply, which is a common requirement for On-board chargers (OBCs) this topology results in the voltage-doubler PFC (V2-PFC) being characterised by a comparably large DC-link voltage ripple at mains frequency. If the DC-link capacitance shall be minimized, for instance to avoid lifetime-limited electrolytic capacitors, two more circuits in addition to the original V2-PFC are proposed for keeping the common-mode-free operation: A balancing circuit (BC), that balances the voltages over the split capacitors and a ripple port (RP), that buffers the 100 Hz power pulsation of the mains. For both circuits the available two bridge legs of the three-phase topology in single-phase operation may be utilized. A 3.7 kW laboratory sample verifies the functionality of the additional circuits in conjunction with the V2-PFC and achieves an efficiency of 95 %.

LLC Converter in Capacitive Operation Utilizing ZCS for IGBTs – Theory, Concept and Verification of a 2 kW DC-DC Converter for EVs - Urbaneck, Daniel; Rehlaender, Philipp; Böcker, Joachim; Schafmeister, Frank (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
LLC resonant converters typically employ power MOSFETs in their inverter stage. The generally weak reverse recovery behaviour of the intrinsic body diodes of those MOSFETs causes significant turn-on losses when being forced to hard commutations. Continuous operation in this way will lead to self-destruction of the transistors. Consequently, zero-voltage switching (ZVS) is essential in a MOSFET-based inverter stage. To ensure ZVS, the LLC converter is operated in the inductive region. On the contrary, IGBTs show dominant turn-off losses and are therefore conventionally not applied in LLC converters typically requiring high switching frequencies to achieve low output voltages. However, if the LLC converter is intentionally designed for capacitive operation, zero-current switching (ZCS) is enabled and thus robust and cost-efficient IGBTs can be applied in the inverter stage. The aim of this work is to investigate the use IGBTs in the inverter of an LLC converter. The theory behind the capacitive operated LLC is derived using a switched simulation model and compared with the fundamental harmonic approximation (FHA). The results prove FHA to be useless for practical converter design. Instead, a stress value analysis based on switched model simulations is proposed to the design a capacitive operated LLC utilizing ZCS. A 2 kW prototype for on-board EV applications was built to verify the theory and design approach. The prototype confirms the derived theory and thus the deployment of IGBTs in the inverter stage of LLC resonant converters. Synchronous rectification turns out to require a specific control solution, but if given the resulting efficiency in the most critical operation point exceeds the value of a MOSFET-based (inductive operated) LLC-design of an identical application. Therefore, this concept should be further developed.

Accurate Torque Control for Induction Motors by Utilizing a Globally Optimized Flux Observer - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Accurate Torque Estimation for Induction Motors by Utilizing a Hybrid Machine Learning Approach - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (2021 IEEE 19th International Power Electronics and Motion Control Conference (PEMC))

Combined Electrical-Thermal Gray-Box Model and Parameter Identification of an Induction Motor - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society)

Gray-Box Loss Model for Induction Motor Drives - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (2021 IEEE 19th International Power Electronics and Motion Control Conference (PEMC))

SootFX: A Static Code Feature Extraction Tool for Java and Android - Karakaya, Kadiray; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

Comparison of Artificial Neural Network and Least Squares Prediction Models for Finite-Control-Set Model Predictive Control of a Permanent Magnet Synchronous Motor - Hanke, Sören; Wallscheid, Oliver; Böcker, Joachim

Thermal Monitoring of Electric Motors: State-of-the-Art Review and Future Challenges - Wallscheid, Oliver (IEEE Open Journal of Industry Applications)

Data-Driven Permanent Magnet Temperature Estimation in Synchronous Motors with Supervised Machine Learning: A Benchmark - Kirchgässner, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Energy Conversion)

gym-electric-motor (GEM): A Python toolbox for the simulation of electric drive systems - Balakrishna, Praneeth; Book, Gerrit; Kirchgässner, Wilhelm; Schenke, Maximilian; Traue, Arne; Wallscheid, Oliver (Journal of Open Source Software)

A Deep Q-Learning Direct Torque Controller for Permanent Magnet Synchronous Motors - Schenke, Maximilian; Wallscheid, Oliver (IEEE Open Journal of the Industrial Electronics Society)

Improved Exploring Starts by Kernel Density Estimation-Based State-Space Coverage Acceleration in Reinforcement Learning - Schenke, Maximilian; Wallscheid, Oliver (arXiv preprint arXiv:2105.08990)

PERMANENT MAGNET SYNCHRONOUS MACHINE TEMPERATURE ESTIMATION USING LOW-ORDER LUMPED-PARAMETER THERMAL NETWORK WITH EXTENDED IRON LOSS MODEL - Gedlu, E. G.; Wallscheid, O.; Böcker, J. (The 10th International Conference on Power Electronics, Machines and Drives (PEMD 2020))

Torque and Inductances Estimation for Finite Model Predictive Control of Highly Utilized Permanent Magnet Synchronous Motors - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Industrial Informatics)

Hegel’s Interpretation of the Liar Paradox - d’Agostini, Franca; Ficara, Elena (History and Philosophy of Logic)
Keywords: History and Philosophy of Science; History

‘Transcendental’ in Kant and Fichte. A Conceptual Shift and its Philosophical Meaning - Ficara, Elena (Fichte-Studien)

The Birth of Dialetheism - Ficara, Elena (History and Philosophy of Logic)

Blogpost "Von der Dankbarkeit über ein offenes Ohr" - Lebock, Sarah
BloKK-Beitrag für das ZeKK, 08.10.2021

Observing 0D subwavelength-localized modes at ~100 THz protected by weak topology - Lu, Jinlong; Wirth, Konstantin G.; Gao, Wenlong; Heßler, Andreas; Sain, Basudeb; Taubner, Thomas; Zentgraf, Thomas (Science Advances)
Topological photonic crystals (TPhCs) provide robust manipulation of light with built-in immunity to fabrication tolerances and disorder. Recently, it was shown that TPhCs based on weak topology with a dislocation inherit this robustness and further host topologically protected lower-dimensional localized modes. However, TPhCs with weak topology at optical frequencies have not been demonstrated so far. Here, we use scattering-type scanning near-field optical microscopy to verify mid-bandgap zero-dimensional light localization close to 100 THz in a TPhC with nontrivial Zak phase and an edge dislocation. We show that because of the weak topology, differently extended dislocation centers induce similarly strong light localization. The experimental results are supported by full-field simulations. Along with the underlying fundamental physics, our results lay a foundation for the application of TPhCs based on weak topology in active topological nanophotonics, and nonlinear and quantum optic integrated devices because of their strong and robust light localization.

Key Point Analysis via Contrastive Learning and Extractive Argument Summarization - Alshomary, Milad; Gurcke, Timon; Syed, Shahbaz; Heinisch, Philipp; Spliethöver, Maximilian; Cimiano, Philipp; Potthast, Martin; Wachsmuth, Henning (Proceedings of the 8th Workshop on Argument Mining)

iClarify - A Tool to Help Requesters Iteratively Improve Task Descriptions in Crowdsourcing - Nouri, Zahra; Prakash, Nikhil; Gadiraju, Ujwal; Wachsmuth, Henning (Proceedings of the Ninth AAAI Conference on Human Computation and Crowdsourcing, HCOMP 2021)

Near-Shortest Path Routing in Hybrid Communication Networks - Coy, Sam; Czumaj, Artur; Feldmann, Michael; Hinnenthal, Kristian; Kuhn, Fabian; Scheideler, Christian; Schneider, Philipp; Struijs, Martijn (25th International Conference on Principles of Distributed Systems, OPODIS 2021, December 13-15, 2021, Strasbourg, France)

Spring Forward, Don't Fall Back: The Effect of Daylight Saving Time on Road Safety - Bünnings, Christian; Schiele, Valentin (The Review of Economics and Statistics)
In this paper, we analyze the effect of light conditions on road accidents and estimate the long run consequences of different time regimes for road safety. Identification is based on variation in light conditions induced by differences in sunrise and sunset times across space and time. We estimate that darkness causes annual costs of more than £500 million in Great Britain. By setting daylight saving time year-round 8 percent of these costs could be saved. Thus, focusing solely on the short run costs related to the transition itself underestimates the total costs of the current time regime.

Online Monitoring des Beschichtungsprozesses im Laser Sintern, Systementwicklung und Einflussanalyse - Klippstein, Sven Helge

Influences of Temperature-Dependent Boundary Conditions on Component Properties in Arburg Plastic Freeforming - Moritzer, Elmar; Hecker, Felix; Elsner, Christian Lennart; Hirsch, André (Proceedings of 36th Annual Meeting of Polymer Processing Society (PPS-36))

Comparison of unidirectional Three- and Four-Wire based Boost PFC-Rectifier Topologies for Non-Isolated Three-Phase EV On-Board Chargers under Common-Mode Aspects - Hagemeyer, Marc; Wallmeier, Peter; Schafmeister, Frank; Böcker, Joachim (Proc. 36th IEEE Applied Power Electronics Conference (APEC))

Transformerless On-Board Chargers at Three- and Single-Phase Operation: Compensation of LF Common-Mode Noise by the Internal DC/DC-Stage - Schafmeister, Frank (Power System Design (PSD) Web Magazine)

Influence of household regeneration techniques on the filtration efficiency of FFP2 and surgical masks in the submicron size range - Tischendorf, Ricardo; Schmid, Hans-Joachim

Influence of Atomization on Particle Formation in Spray Flames - Tischendorf, Ricardo; Schmid, Hans-Joachim; Bieber, M.; Reddemann, M.; Kneer, R.; Fröde, F.; Grenga, T.; Pitsch, H.

Einfluss der Zerstäubung auf die Partikelsynthese in Sprayflammen - Tischendorf, Ricardo; Schmid, Hans-Joachim; Bieber, M.; Reddemann, M.; Kneer, R.; Fröde, F.; Grenga, T.; Pitsch, H.

Simplifying Robot Programming using Augmented Reality and End-User Development - Yigitbas, Enes; Jovanovikj, Ivan; Engels, Gregor (Proceedings of the 18th IFIP TC13 International Conference on Human-Computer Interaction (INTERACT 2021))

Using Augmented Reality for Enhancing Planning and Measurements in the Scaffolding Business - Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Proceedings of the 13th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS 2021))